Limited liability, asymmetric taxation, and risk taking: Why partial tax neutralities can be harmful - Ralf Ewert; Rainer Niemann (Center for Economic Studies and ifo Institute (CESifo), 2010)
We examine the combined effects of asymmetric taxation and limited liability on optimal risk taking of investors. Given an optimal risk level in the pre-tax case under full liability, loss-offset restrictions reduce, and limited liability enhances the incentives for taking risk. For every degree of limited liability we can find corresponding loss-offset limitations inducing the same optimal risk level as in the reference case. Thereby we get tax neutrality with respect to risk taking. We show that tax neutrality with respect to risk taking is incompatible with tax neutrality with respect to the choice of the legal form. In our model, full liability requires symmetric taxation and limited liability requires asymmetric taxation of profits and losses.
Keywords: H25; M41; 330; limited liability; loss-offset; tax neutrality; risk taking; Beschränkte Haftung; Risikoaversion; Unternehmensbesteuerung; Steuerwirkung; Rechtsformwahl; Theorie